Pengetahuan Remaja Di Kota Manado Tentang Penyakit Degeneratif - MOKALU, FEREN LEDYA; Masi, Gresty Natalia Maria; Sirait, Imelda (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2023)
Background. Degenerative disease is a condition of organs and body system that getting worse over time. The level of knowledge of the teenagers about degenerative diseases is an important information for medical workers in the planning process and determination of medical services to improve health quality. Purpose. To discover the knowledge of the teenagers in Manado City about degenerative diseases, which are diabetes mellitus and hypertension. Method. Using a descriptive quantitative approach. A total sample of 395 teenagers, using the DKQ-24 questionnaire (Diabetes Knowledge Questionnaire) and the knowledge questionnaire about hypertension. Results. 93 teenagers (23.5%) had good knowledge of diabetes mellitus, 300 teenagers (75.9%) sufficient category, 2 teenagers (0.5%) poor category. The knowledge of the teenagers about hypertension was in the good category, 341 teenagers (86.3%), in the moderate category, 54 teenagers (13.7%), in the less category, 0 teenagers (0%). Conclusion. Knowledge of the teenagers in Manado City about diabetes mellitus is in the sufficient category and the knowledge of the teenagers in Manado City about hypertension is in the good category. Keywords : Degenerative Disease, Knownledge, Teenagers